UNSUR KERUGIAN DALAM UNJUSTIFIED ENRICHMENT UNTUK MEWUJUDKAN KEADILAN KOREKTIF (CORRECTIVE JUSTICE) - Faizal Kurniawan; Peter Mahmud Marzuki; Erni Agustin; Rizky Amalia (Yuridika, 2018)
Recent development to claim damages on the basis of either wanprestatie or onrechtmatige daad would not provide saticfactory grounds to the question of justice. There will be a situation in which that no one shall be unjustly enriched at the expense of another which all outside the scope of contract and tort. This has led to the existence of an independent legal doctrine known as unjust enrichment. It is among the most debated private law subjects today in asking for justice. Corrective justice brings to the remedial relation between the plaintiff and the defendant; it is solely concerned with the norm of justice that provides reasons to restitution. Corrective justice properly evaluates the structure of injustness to the both sides, the plaintiff and the defendant. It gives effect to restitutionary proprietary interests rather than compensatiton. This article elaborates the law of unjust enrichment as ground for restitution in conjunction with the corrective justice. Furthermore, this article focuses on the theoritical foundation of corrective justice to meet the unjustified enrichment criteria.